Voltammetric Synthesis of Conducting Polymer Polypyrrole and Its Response Characteristic to Alcohol - Susi Nurqomariyah; Asnawati Asnawati; Neran Neran; Siswoyo Siswoyo (Jurnal ILMU DASAR, 2015)
Conducting polymer is a used material for many purposes, including active compound of chemical sensor. Polypyrrole, one type of conducting polymers, is frequently used because of its advantages, namely owing high conductivity, strong mechanical properties and relatively stable compound.  This research was aimed to develop an alcohol sensor based on polypyrrole. Electropolymerisation of the polypyrrole was carried out using cyclic voltammetric technique. This research investigated some parameters electropolymerisation, namely variation of dopant electrolyte concentration, potential scan-rate, surface morphology of the polymer resulted, characteristic of the sensor performance when exposed to some alcohol compounds. According to the result of investigation, it was found that variation of potential scan-rate and dopant concentration has significant effect to the electropolymerisation process as well as to the resulted polymer, as indicated by the voltammogram profiles, the surface morphology of the resulted polymer and the response of resistance change of the polymer when exposed to the alcohol compounds.Keywords: polypyrrole, conducting polymer, alcohol sensor, cyclic voltammetry, electropolymerisation.